On the use of field RR lyrae as galactic probes: IV. New insights into and around the Oosterhoff dichotomy* - Fabrizio, Michele; Braga, Vittorio Francesco; Crestani, J.; Bono, G.; Ferraro, I.; Fiorentino, G.; Iannicola, G.; Preston, G. W.; Sneden, C.; Thévenin, F.; Altavilla, G.; Chaboyer, B.; et al. (The astrophysical journal, 2021)
We discuss the largest and most homogeneous spectroscopic data set of field RR Lyrae variables (RRLs) available to date. We estimated abundances using both high-resolution and low-resolution (ΔS method) spectra for fundamental (RRab) and first overtone (RRc) RRLs. The iron abundances for 7941 RRLs were supplemented with similar estimates that are available in the literature, ending up with 9015 RRLs (6150 RRab, 2865 RRc). The metallicity distribution shows a mean value of 〈[Fe/H]〉 = −1.51 ± 0.01, and σ(standard deviation) = 0.41 dex with a long metal-poor tail approaching [Fe/H] ≃ − 3 and a sharp metal-rich tail approaching solar iron abundance. The RRab variables are more metal-rich (〈[Fe/H]〉ab = −1.48 ± 0.01, σ = 0.41 dex) than RRc variables (〈[Fe/H]〉c = −1.58 ± 0.01, σ = 0.40 dex). The relative fraction of RRab variables in the Bailey diagram (visual amplitude versus period) located along the short-period (more metal-rich) and the long-period (more metal-poor) sequences are 80% and 20%, while RRc variables display an opposite trend, namely 30% and 70%, respectively. We found that the pulsation period of both RRab and RRc variables steadily decreases when moving from the metal-poor to the metal-rich regime. The visual amplitude shows the same trend, but RRc amplitudes are almost two times more sensitive than RRab amplitudes to metallicity. We also investigated the dependence of the population ratio (N c /Ntot) of field RRLs on the metallicity and we found that the distribution is more complex than in globular clusters. The population ratio steadily increases from ∼0.25 to ∼0.36 in the metal-poor regime, it decreases from ∼0.36 to ∼0.18 for −1.8 ≤ [Fe/H] ≤ −0.9 and it increases to a value of ∼0.3 approaching solar iron abundance.
Gesehen am 15.12.2021
Keywords: Milchstraßensystem; RR-Lyrae-Stern